The Influence of Consumer Motivation and Attitudes on Xpander Car Purchasing Decisions - Wildan, M Ichwan; Afnina, Afnina (CV. Rayyan Dwi Bharata, 2024)
This research wants to know the influence of consumer motivation and attitudes on the decision to purchase an Xpander car in Langsa, Aceh Province. This research uses a quantitative descriptive research design. The sampling technique was accidental sampling, totaling 53 respondents who the researchers met by chance at the Langsa City shopping center. The analysis tool uses multiple linear regression. The research results show that consumer motivation is high, consumer attitudes are positive, and purchasing decisions are in accordance with high consideration by consumers. The findings stated that there was an influence of consumer motivation on purchasing decisions of 0.841, while the influence of consumer attitudes was 0.563. There was an influence of consumer motivation and consumer attitudes on purchasing decisions of 53.90%. Based on the research results, it can be seen that the factor that dominates purchasing decisions is consumer motivation because the regression value is 0.841 which is greater than consumer attitude which is only 0.056. The findings in this research show that it is true that consumer motivation and attitudes influence purchasing decisions. It is recommended that Xpander car manufacturers continue to strive to increase motivation so that consumer attitudes towards purchasing decisions improve.